A Multi-Disciplinary Examination of Psycho-Physiological Performance Among Youth and Junior Ball Sport Athletes: A Systematic Review - József Márton Pucsok; Andrea Lentene Puskas; Katalin Varga; Gabriella Perenyi; Eva Bacsne Baba; Laszlo Balogh (Sapientia Publishing Group, 2018)
Objectives The primary purpose of our review was to systematically review the evolution of psycho-physiological performance analysis. Our secondary aim was to investigate the role of specific, multi-disciplinary performance indicators to identify future talents in the sport of soccer, handball and basketball. Methods A review protocol was set up in order to avoid individual bias and ensure an efficient searching prodedure. This enabled a search strategy to define which literature was to be included or excluded from our research. Certain inclusion criteria were identified, before performing a search using three electronic databases (Web of Science, ScienceDirect, and Google Scholar) and reference lists for English-language articles, published from the year 1980 till 2017. Results The comprehensive search yielded 82 documents to be relevant to our purpose of the study, according to our inclusion criteria criteria, 58 were fully-reviewed and referred to in our study. As we previously expected, the review of related literature resulted investigations involving mostly soccer and basketball players, studies conducted on handball players are significantly fewer. The majority of those studies examined physical performance characteristics via various field test. Conclusions We concluded that further analysis is necessary to identify relevant psycho-physiological performance indicators, in order to properly enhance sports performance in the younger athlete population and in general too. Vienna Test System protocols may offer a great potential to provide valuable information for athletes and their coaches to enhance athletic performance. Future research should focus on specifically identify Vienna Test System test protocols that may be linked to each particular sport.